INDEKS BUDI PEKERTI PRIBADI DALAM KARYA RAJA ALI HAJI - Abdul Malik; Isnaini Leo Shanty (Jurnal Kiprah, 2017)
This paper is a result of the research of personal character index in the works of Raja Ali Haji. The paper aims to: (1) analyze the character index within selves in the works of Raja Ali Haji, (2) investigate the relationship between personal character index and the teachings of Islam in the works of Raja Ali Haji, and (3) analyze the semiotics class of personal character index in the works of Raja Ali Haji. This study applies semiotics theory of Charles Sanders Peirce. An analysis was performed on five works of Raja Ali Haji, namely Syair Abdul Muluk (The Poem Abdul Muluk), Gurindam Dua Belas (The Twelve Couplets), Thamarat al-Muhimmah (The Desired Fruits), Tuhfat al-Nafis (The Precious Gift), and Syair Sinar Gemala Mestika Alam (The Poem Shining Natural Gem). The data were analyzed using content analysis technique. The research results found that (1) Raja Ali Haji’s works contain nineteen personal character indexes, (2) the values of personal character index is interrelated to Islamic teachings, and (3) semiotics class of personal character index in the works of Raja Ali Haji is comprised of rheumatic iconic qualisign, rheumatic indexical sinsign, dicent indexical legisign, and argument. As a result, Raja Ali Haji’s works can be referred to as a way of life and is worthy of use as learning materials for character education sourced from the literary works